Типологія ідіом в когнітивно-генетичному аспекті - Жуйкова, Маргарита Василівна; Zhujkova, Margaryta ("Мовознавство", Київ, 2004)
У статті пропонується розрізняти дві генетично відмінні групи ідіом: такі, що виникли як знаки непрямої номінації шляхом переосмислення вільних словосполучень чи речень, і такі, які утворились у мовленні незалежно від вільних словосполучень, одразу як семантично цілісні одиниці, значення яких співвідноситься з ситуацією, яку вони позначають. In the article the author proposes to distinguish two genetically different groups of idioms. The first group consists of idioms that evolved as signs of indirect nomination from unbound word-combinations or sentences. The second group is comprised of idioms that entered the language independently as semantically integral units whose meaning correlates with the situation they refer to.
A typology of idioms in the cognitive-genetical aspect
Keywords: ідіома, механізми ідіомотворення, ментальний образ, імплікація, вивідне знання; idiom, mechanisms of idiom formation, mental image, implication, inferential knowledge.